Lessons learned in the implementation of a study to evaluate intestinal colonization with antibiotic-resistant bacteria in communities and hospitals in India - Girish Kumar Chethrapilly Purushothaman; Sathya Narayanan Gopalakrishnan; Tarun Bhatnagar; Swathi Subbiah Sankarraj; V. Sindhuja; Valan A. Siromany; Daniel VanderEnde; Ahmed Babiker; Paul Malpiedi; Susan Bollinger; Ashley Styczynski; Rachel M. Smith (Frontiers in Public Health, 2026)
Introduction Measuring colonization with antibiotic-resistant bacteria (ARB) and associated risk factors in community members and hospitalized patients is crucial to combating the spread of ARB. The Antibiotic Resistance in Communities and Hospitals (ARCH) study, conducted in multiple countries, aimed to assess the prevalence of and risk factors for intestinal colonization with ARB of public health importance. Methods The prevalence and risk factors of intestinal colonization with ARB was determined through and participant surveys among 757 community and 556 hospitalized adult individuals and bacterial isolation from their stool specimens. This paper focuses on the implementation experience of the ARCH study in India. Results Implementing robust AMR studies in low- and middle-income country settings is very challenging. Socio-cultural factors likely resulted in a high refusal rate (Community—49%; Hospital—59%) for stool sample collection. In the laboratory, discordant results from Vitek®2 Compact had to be confirmed using reference methods. Study implementation was further complicated by the COVID-19 pandemic, leading to delays in participant recruitment, suspension of fieldwork during lockdowns, and interruption of laboratory testing due to supply chain limitations. Taboos around stool collection and handling were overcome with the help of members of the local administrative body in the community and medical staff in the hospitals. Conducting an initial pilot exercise followed by periodic reviews of the study’s progress proved beneficial in limiting errors and challenges during the study, and precautionary steps were taken during data management to ensure data quality. Conclusion Implementation challenges were addressed through early stakeholder engagement, pilot testing of study procedures, robust laboratory quality assurance mechanisms, and integrated electronic data management systems. Lessons learned from this study may inform future AMR surveillance initiatives in resource-limited settings.